PENDEKATAN SOFT SYSTEM METHODOLOGY DALAM PENGEMBANGAN COMMUNITY PARENTING DI DESA MIGRAN PRODUKTIF JEPARA, LAMPUNG TIMUR - Fitriani, Yuyun (Jurnal Ilmu Administrasi Negara (JUAN), 2022)
The Desmigratif Program is a breakthrough effort by the Ministry of Manpower to provide protection for Indonesian Migrant Workers (PMI) in villages that are PMI pockets. The Desmigratif Program has four pillars. First, the establishment of employment information centers and migration services. Second, develop productive businesses that involve PMI families. The third is to form a parenting community and child development (Community Parenting). Fourth is the formation and development of cooperatives/financial institutions. This study uses a soft system methodology (SSM). SSM is a suitable methodology to assist an organization in clarifying their goals and then designing a system of human activities to achieve those goals. The results showed that efforts to develop community parenting in the Productive Migrant Village of Jepara failed. The failure was caused by low stakeholder communication, resources that were not utilized properly, and low community participation. Some of the causes of these failures are solved through the construction of a conceptual model which is a step-by-step scenario to solve the problem. The initial step of SSM activities was carried out by resocializing the Desmigratif and restructuring the team as well as digging up PMI family data to identify strategies so that they were right on target. Furthermore, to build integration and formal access to external parties to participate as well as the compliance of all stakeholders.